Practice Rehearsal Pairs Strategy: Student Learning Outcomes in the IPAS Subject at Primary Schools - Mustika, Rini; Akmansyah, Muhammad; Yulianti, Yulianti (Education and Talent Development Center Indonesia (ETDC Indonesia), 2025)
The intent of this study is to determine the process of improving student learning outcomes through the practice rehearsal pairs strategy in elementary school students. This type of research uses classroom action research. The subjects in this study were teachers and fifth-grade students, with a total of 20 fifth-grade students at Primary School 2 Ratu Abung, North Lampung. Data collection techniques used tests, observation, and documentation. The data analysis used a quantitative description. The study found that using the practice rehearsal pairs strategy learning model (paired practice) to improve student learning outcomes in IPAS can be seen in two ways: the teacher, in the cycle I to cycle II teachers who use the practice rehearsal pairs strategy learning model (paired practice). The analysis reveals that learning activities in Cycle I are dynamic. In cycle. Eight students are not good (46.66%), four are good (33.34%), five are good (10%), and three are excellent (10%). Cycle II has 5 outstanding pupils (16.66%) and 15 forceful students (81%). In the practice rehearsal pairs strategy learning model from cycle I to cycle II, student enthusiasm and activity always increase, as shown by observations and tests of student learning outcomes, so learning can run smoothly and conducively and achieve learning objectives.